Pengaruh Digital Marketing, Brand Image dan Promosi terhadap Keputusan Pembelian pada Kentucky Fried Chicken (KFC) Kota Probolinggo - Saiful Rizal; Adi Putra Darmawan; Beny Yusman; Sri Nurhasana; Ummi Latifah; Isyvina Unaizah Royya (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to examine the effect of digital marketing, brand image, and promotion on consumer purchasing decisions at Kentucky Fried Chicken (KFC) in Probolinggo City. This research employs a quantitative method with a causal associative approach. The sample consists of 100 respondents who are KFC consumers in Probolinggo City, selected using purposive sampling. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression with the assistance of SPSS version 26. The results indicate that digital marketing, brand image, and promotion have a significant effect on purchasing decisions both partially and simultaneously. Brand image is the most dominant variable, with the highest t-value of 7.726. These findings suggest that improving digital marketing strategies, strengthening brand image, and implementing effective promotional activities can enhance consumer purchasing decisions. However, this study is limited to three independent variables and a specific research scope, which limits generalization. Therefore, companies are advised to improve marketing strategies, and future research should include additional variables and broader research areas.